2018
DOI: 10.3390/vetsci5010012
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Identification of Eimeria Species in Broiler Chickens in Trinidad, West Indies

Abstract: Coccidiosis is an intestinal disease of chickens of major economic importance to broiler industries worldwide. Species of coccidia found in chickens include Eimeria acervulina, Eimeria brunetti, Eimeria maxima, Eimeria mitis, Eimeria necatrix, Eimeria praecox, and Eimeria tenella. In recent years, polymerase chain reaction (PCR) has been developed to provide accurate and rapid identification of the seven known Eimeria species of chickens. The aim of this study was to use species-specific real-time PCR (qPCR) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 15 publications
1
17
0
Order By: Relevance
“…The most prevalent species among broiler farms in this study was E. tenella (68.4%), which is in agreement with other studies that have reported a high prevalence that ranges from 80.67% to 100% in Anhui Province, China, Trinadad and Indonesia (Brown et al 2018 ; Hamid et al 2018 ; Huang et al 2017 ). The high prevalence of E. tenella poses a major concern to the health status of chickens because it is associated with caecal lesions causing haemorrhage, oedema and anaemia (Iacob & Duma 2009 ).…”
Section: Discussionsupporting
confidence: 92%
“…The most prevalent species among broiler farms in this study was E. tenella (68.4%), which is in agreement with other studies that have reported a high prevalence that ranges from 80.67% to 100% in Anhui Province, China, Trinadad and Indonesia (Brown et al 2018 ; Hamid et al 2018 ; Huang et al 2017 ). The high prevalence of E. tenella poses a major concern to the health status of chickens because it is associated with caecal lesions causing haemorrhage, oedema and anaemia (Iacob & Duma 2009 ).…”
Section: Discussionsupporting
confidence: 92%
“…having been shown to be common in broilers on Trinidad. 6 We found no reports of noninfectious causes of lesions in chickens from the Caribbean.…”
Section: Introductionmentioning
confidence: 81%
“…Most of the chickens (n = 66, 82%) had at least 1 helminth species, and 55 (68%) had coinfections with cestodes and nematodes (Figs. [2][3][4][5][6][7][8][9]. Cestodes were present in 64 chickens (79%), mainly Raillietina echinobothrida followed by R. tetragona and Amoebotaenia cuneata (A. sphenoides), with Choanotaenia sp.…”
Section: Parasitologymentioning
confidence: 99%
“…Coccidiosis is a parasitic disease caused by a protozoan known as Eimeria (Brown-Jordan et al ., 2018). Guven et al .…”
Section: Introductionmentioning
confidence: 99%
“…There are seven known Eimeria species, each of which differs significantly by both morphological and physiological means. The identification of each species present within an infection is vital to develop species-specific treatment, as all Eimeria species may not be susceptible to standard treatment (Guven et al ., 2013; Brown-Jordan et al ., 2018; Fatoba and Adeleke, 2018; Sharma et al ., 2018). The identification of Eimeria species is not only required to diagnose and control the disease but is also required for population genetics, biology and epidemiological studies (Huang et al ., 2017).…”
Section: Introductionmentioning
confidence: 99%